Numerical Study of Wall Ventilation in a Transonic Wind Tunnel - Goffert,Bruno (2015)
ABSTRACT: Transonic wind tunnels (TWT) are sophisticated tools for the investigations of flows with Mach numbers of order one. The most characteristic feature of a facility such as this is, for sure, the openings in the walls of the test section. The openings in the walls permit the proper relief effect, and this, on the other hand, makes possible the experimentation at the transonic range. The results to be presented in this paper correspond to an analysis of the flow in the test section of a TWT containing a NACA 0012 airfoil. Both numerical and experimental investigations were conducted. For the numerical investigation, a three-dimensional, finite-difference code, based on the diagonal algorithm, was employed, whereas for the experimentation, the classical static-pressure taps as well as the pressure sensitive paint (PSP) techniques were used. The classical static-pressure tap method is indicated as PSI technique. The pressure distributions were investigated for Mach numbers in the range of 0.6 - 0.8 and angles of attack from 0º up to 8º. The relief effect due to the slots, which provides for avoiding choking effects, is clearly demonstrated when one compares the flow along both solid and perforated walls. In the first part of this research report, the main focus will be on the numerical results. Notwithstanding this, and for comparison purposes, some experimental results will be called upon here, together with some literature data.